Detouring dynamic routing holes in stationary wireless sensor networks in the presence of temporarily misbehaving nodes. (16th June 2015) - Kar, Pushpendu; Misra, Sudip
Summary: In this work, we propose a scheme, named BRIDGE, to bypass dynamic routing holes arising in stationary wireless sensor networks in the presence of temporarily misbehaving nodes such as dumb1 2 or transfaulty nodes. The affected nodes behave normally after the resumption of favorable environmental conditions. Therefore, both dumb and transfaulty behaviors of sensor nodes are dynamic in nature. The nodes in these networks get temporarily isolated from the network, when they behave as dumb or transfaulty. Because of the presence of nodes with such behavior, dynamic communication holes may occur in the network, which are formed or removed and thus increase or decrease in size with time. Connectivity re‐establishment procedures can mitigate holes by re‐connecting isolated nodes with the network after activating the intermediate sleep nodes, adjusting the communication range of intermediate nodes, or by using an alternative communication mode. However, such procedures cannot always re‐establish connectivity because of the lack of neighbor nodes in reduced or adjusted communication range. Therefore, routing schemes using greedy forwarding approaches need to bypass holes to avoid the data packets from getting stuck at the boundary nodes and efficiently delivering them to the sink. However, the existing hole avoidance schemes consider holes as static. The proposed scheme, BRIDGE, detects hole boundary and bypasses routing traffics in the dynamic hole scenario. In the proposed scheme, a boundary node selects the next hop based on the minimum distance from all the neighbor nodes to the destination node, although this minimum distance is more than the distance to the destination from the node itself. Simulation results show that the performance of the proposed scheme degrades with the increase in hole area. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : In this work, we propose a scheme, named BRIDGE, to bypass dynamic routing holes arising in stationary wireless sensor networks in the presence of temporarily misbehaving nodes such as dumb or transfaulty nodes. The proposed scheme, BRIDGE, detects a hole boundary and bypasses routing traffics in the dynamic hole scenario. In the proposed scheme, a boundary node selects the next hop based on the minimum distance from all the neighbor nodes to the destination node, although this minimum distance is more than the distance to the destination from the node itself.